Impact of Land‐Sea Thermal Contrast on the Inland Penetration of Sea Fog Over the Coastal Area Around the Korean Peninsula. Issue 12 (16th June 2018) - Lee, Ho‐Yeon; Chang, Eun‐Chul
Abstract: Based on the difference between sea surface temperature (SST) and sea air temperature (SAT), sea fog can be classified as cold sea fog (SST < SAT) or warm sea fog (SST > SAT). First, two sea fog events over the Yellow Sea are selected and simulated using Weather Research and Forecasting model. The two sea fogs are designated as cold and warm types, and cooling and moistening rates of each case are calculated to understand the contributions of major factors to the sea fog formation. Turbulence plays a role in the cooling (warming) of the sea air, while advection is responsible for sea air warming (cooling) during the cold (warm) sea fog event. Thus, these two effects cancel each other out. However, the longwave radiative cooling effect is as stronger as or stronger than the other effects in both cases. We conducted sensitivity tests of SST and land skin temperature, which induced obvious changes in turbulent heat flux and land‐sea thermal contrast, respectively. In the increased (decreased) SST experiments, sea fog evaporates (expands) because of more (less) heat transfer from sea to air. The land skin temperature experiments show that increases (decreases) in land‐sea air temperature differences hinder (favor) sea fog penetration. Key Points: Turbulence plays the following role in sea fog formation: Sea air becomes cooler (warmer) and drier (moister) in the cold (warm) sea fog Increases (decreases) in sea surface temperature show reductions (increases) in cloud water mixing ratios and less (more) stable sea fog layers Increases (decreases) in land‐sea air temperature differences hinder (favor) the inland penetration of sea fog